THU0073 Loss of Tyrosine Kinases Leads to Enhanced Osteoclastogenesis in a Murine Model of Rheumatoid Arthritis. (23rd January 2014) - Bonelli, M.; Blüml, S.; Böhm, C.; Hladik, A.; Goncalvesalves, E.; Ellmeier, W.; Smolen, J. S.; Scheinecker, C.
Abstract : Background: Tyrosine Kinases (TEC) family members like Btk and Tec play an important role in osteoclastogenesis. However, little is known about the role of Tec on osteoclast under auto-inflammatory conditions such as in rheumatoid arthritis (RA). Objectives: We therefore investigated the role of Tec in the collagen induced arthritis model (CIA) of RA. Methods: CIA was induced in wild-type (WT) and Tec-/- mice at week 10 of age by immunization with chicken collagen II (CII). After 3 weeks mice received a booster injection of CII. Mice were scored for paw swelling and grip strength. Anti-CII antibody levels were determined by ELISA. After 60 days all animals were sacrificed and paraffin sections of the affected joints were analyzed for histomorphologic signs of inflammation, cartilage and bone destruction. To analyse in vitro osteoclastogenesis calvarial osteoblasts from WT and Tec-/- mice were stimulated with Vitamine D and dexamethasone and cocultured with bone marrow cells from WT or Tec-/- mice. Cells were stained with TRAP and mononuclear cells with more than 3 nuclei were defined as osteoclasts. Results: All animals immunized with CII developed serum anti-CII antibodies. No difference was observed for paw swelling and grip strength between Tec-/- and WT animals. However, in contrast to the clinical data, histological analysis revealed a significant increase in osteoclasts numbers in Tec-/- as compared to WT mice. In line, the local bone destruction was significantly increased in Tec-/- mice compared to wt mice. The amount of synovial inflammation, however, was not different between the groups. To further elucidate this mechanism we performed osteoblast assays where we observed increased numbers of TRAP positive cells in Tec-/- mice, suggesting that osteoblasts from Tec-/- mice induce osteoclastogenesis more efficiently than WT osteoblasts. Conclusions: These results show that Tec is an important regulator of osteoclast differentiation and local bone destruction in inflammatory arthritis. Furthermore coculture experiments suggest that Tec regulates osteoblast function in an inflammatory environment. Disclosure of Interest: None Declared